HONEY IN THE TREATMENT OF PERIODONTITIS - KANAKAM ELIZABETH THOMAS (International Journal of Pharma and Bio Sciences, 2014)
From ancient times, honey is being used as a therapeutic agent apart from its wide use as a sweetener. Honey is known to have antibacterial and anti-inflammatory property. Honey is used widely in the treatment of burns, to heal wounds, gastritis, ulcers and diarrhea and also in veterinary use. Today honey is available as candies as well as in gelled form. 90% of human population suffers from mild gingivitis to chronic periodontitis in their life time. As bacteria are becoming increasingly resistant to antibiotics newer generation drugs are being prescribed by the dentist. Hence research has turned in finding newer alternative therapy, which can be easily accessed and affordable to common man. Honey is a natural sweetener and can be used as an alternative in treatment of periodontal infections.